Axial variability of pattern formation in Rayleigh-Bénard convection: MRI velocimetry in a low aspect ratio cylinder. (November 2020) - Skuntz, Matthew E.; Pelkie, Brenden G.; Codd, Sarah L.; Anderson, Ryan; Seymour, Joseph D.
Abstract: Natural convection is a fundamental hydrodynamic instability and a template process for the study of pattern formation. It is also an important mode of energy transport in natural geophysical and environmental systems, as well as technological applications. In solar heating devices, pasteurization processes, industrial mixing, and pebble-bed nuclear reactors, low aspect ratio systems of greater depth than width are widely used for their favorable convection properties. Here, magnetic resonance imaging was used to quantify the axial spatial variation of flow patterns in a narrow cylinder. Fluid velocity maps were acquired in multiple transverse and longitudinal planes. It is shown that the flow patterns vary significantly as a function of the height above the heated bottom boundary. The large scale circulation varies among predicted azimuthal mode patterns. Azimuthal 180 o reorientation of the upward and downward flow cells was observed over short axial distances. The complex circulation patterns observed suggest acquisition of velocity data in only one plane could lead to mischaracterization of flow patterns in low aspect ratios systems, an aspect of the current literature which is lacking quantification. A preliminary computational fluid dynamics model in STAR-CCM+, corroborated by the experimental results, provided velocity and temperature data for the full fluid column height. Together these results indicate the need for further investigation into circulation characteristics in long narrow cylinders. Enhanced understanding of these rapid axial variations in flow pattern will allow better modeling of heat and mass transport in low aspect ratio natural convection flows.